PENGARUH PROFITABILITAS, STRUKTUR MODAL, DAN UKURAN PERUSAHAAN TERHADAP NILAI PERUSAHAAN - AJIE WASKITO NUGROHO; Batara Daniel Bagana (Kompak :Jurnal Ilmiah Komputerisasi Akuntansi, 2023)
This study aims to examine the effect of profitability, capital structure, and firm size on the value of food and beverage manufacturing companies listed on the Indonesia Stock Exchange for the 2018-2021 period. The method of determining the sample used is purposive sampling. By using several predetermined criteria, this study used 29 food and beverage sub-sector manufacturing companies. The data analysis technique used in this study is multiple linear regression analysis. The results in this study indicate that: 1) profitability has a positive effect on firm value, 2) capital structure has no effect on firm value, 3) firm size has no effect on firm value.